2009
DOI: 10.1002/cncr.24286
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐finding study of 153Sm‐EDTMP in patients with poor‐prognosis osteosarcoma

Abstract: BACKGROUND: Samarium‐153 ethylenediaminetetramethylene phosphonic acid (153Sm‐EDTMP) has been used to treat patients with high‐risk osteosarcoma. The purpose of the current study was to determine the maximally tolerated dose of 153Sm‐EDTMP that permits hematopoietic recovery within 6 weeks. METHODS: Patients with recurrent or refractory osteosarcoma with bone metastases were enrolled in this study. Subjects were treated with increasing doses of 153Sm‐EDTMP, beginning with 1.0 millicuries (mCi)/kg and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…In a subsequent phase II study designed to study the safety and response of high-risk osteosarcoma to a high dose of 153 Sm-EDTMP, 11 of 13 patients who participated in the phase I study were found eligible to receive a second high dose (tandem dose) of 153 Sm-EDTMP. The clinical trial details and the treatment plan have been described by Loeb et al (2,3). Briefly, patients were included in the study if they had a positive 99m Tc-methylene diphosphonate bone scan finding; autologous hematopoietic stem cells were collected before the first treatment with 153 Sm-EDTMP (low dose).…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent phase II study designed to study the safety and response of high-risk osteosarcoma to a high dose of 153 Sm-EDTMP, 11 of 13 patients who participated in the phase I study were found eligible to receive a second high dose (tandem dose) of 153 Sm-EDTMP. The clinical trial details and the treatment plan have been described by Loeb et al (2,3). Briefly, patients were included in the study if they had a positive 99m Tc-methylene diphosphonate bone scan finding; autologous hematopoietic stem cells were collected before the first treatment with 153 Sm-EDTMP (low dose).…”
Section: Methodsmentioning
confidence: 99%
“…For more detail on CRM designs and for applications published in clinical journals, please see additional references (28, 29). …”
Section: Overviewmentioning
confidence: 99%
“…This study illustrates how pediatric trial consortia could develop this model ( 9 ). A new radionucleotide therapy for pediatric osteosarcoma (Samarium-153-EDTMP) has already been tested using this trial design ( 10 ). The Pediatric Brain Tumor Consortium has also used a modified CRM to evaluate a gamma-secretase inhibitor (NOTCH pathway) in CNS tumors ( 11 ).…”
Section: Identifying a Safe Dosementioning
confidence: 99%